The potential of regulatory T cell-based therapies for alopecia areata - Wan, Sheng; Xu, Wen; Xie, Bo; Guan, Cuiping; Song, Xiuzu (Frontiers in Immunology, 2023)
Cytotoxic T lymphocyte has been a concern for the etiopathogenesis of alopecia areata (AA), some recent evidence suggests that the regulatory T (Treg) cell deficiency is also a contributing factor. In the lesional scalp of AA, Treg cells resident in the follicles are impaired, leading to dysregulated local immunity and hair follicle (HF) regeneration disorders. New strategies are emerging to modulate Treg cells’ number and function for autoimmune diseases. There is much interest to boost Treg cells in AA patients to suppress the abnormal autoimmunity of HF and stimulate hair regeneration. With few satisfactory treatments therapeutic regimens available to AA, Treg cell-based therapies could be the way forward. Specifically, CAR-Treg cells and novel formulations of low-dose IL-2 are the alternatives.